Problems of the transborder spatial planning in the North-West of Russia - Fedorov, Gennady (Louvain-la-Neuve: European Regional Science Association (ERSA), 2014)
Regional planning in Russia includes strategic and spatial planning. The spatial planning is implemented in accordance with the Town Planning Code of the Russian Federation (2004) at the federal, regional and municipal level. It installs functional zones, zones of planned capital construction objects for state or municipal needs, zones of special use conditions. There have been identified and are being studied many possibilities of development and implementation of joint projects of territorial planning of subjects of Northwest of Russia with border countries. Unfortunately, Russia is extremely sluggish in participation in the program VASAB, while in the program Interreg IV (2007-2013), implemented within the framework of the European Neighbourhood and Partnership Instrument - Interreg IVA 'The Baltic Sea Region' Russian organizations are involved only as associate members. However, Russia is involved in cross-border cooperation programs such as Interreg IVB: 'Kolarctic', 'Karelia', 'South-East Finland / Russia', 'Estonia / Latvia / Russia', 'Poland / Lithuania / Russia'. Precondition for expanding and deepening joint development is activities of 7 Euroregions. There is the definite value in the Local border traffic between Russia (the Kaliningrad region) and neighboring provinces of Poland. There are a number of specific proposals, developed by scientists from Russia, Poland, Finland, the Baltic countries in the development of both national and international projects. Among them are: the formation of the South-Baltic and East-Baltic growth triangles, the creation of a bipolar system of territorial Tricity (Gdansk ? Gdynia ? Sopot) ? Kaliningrad and tripolar system, including also Klaipeda, the cross-border cluster on both sides of the Russian-Estonian border, common resources-use of Vistula Bay and its coast by Russia and Poland, increased production functions of Euroregions, the formation of cross-border regions, etc. Preparation of joint projects of territorial planning in the new Cross-border cooperation ...